Long-term outcomes after video-assisted thoracic surgery (VATS) lobectomy versus lobectomy via open thoracotomy for clinical stage IA non-small cell lung cancer - Higuchi, Mitsunori (BioMed Central, 2014)
BACKGROUND: Video-assisted thoracic surgery (VATS) lobectomy is a standard treatment for lung cancer. This study retrospectively compared long-term outcomes after VATS lobectomy versus lobectomy via open thoracotomy for clinical stage IA non-small cell lung cancer (NSCLC). METHODS: From July 2002 to June 2012, 160 patients were diagnosed with clinical stage IA NSCLC and underwent lobectomy. Of these, 114 underwent VATS lobectomy and 46 underwent lobectomy via open thoracotomy. RESULTS: The 5-year disease-free survival (DFS) rate was 88.0% in the VATS group and 77.1% in the thoracotomy group for clinical stage IA NSCLC (p = 0.1504), and 91.5% in the VATS group and 93.8% in the thoracotomy group for pathological stage IA NSCLC (p = 0.2662). The 5-year overall survival (OS) rate was 94.1% in the VATS group and 81.8% in the thoracotomy group for clinical stage IA NSCLC (p = 0.0268), and 94.8% in the VATS group and 96.2% in the thoracotomy group for pathological stage IA NSCLC (p = 0.5545). The rate of accurate preoperative staging was 71.9% in the VATS group and 56.5% in the thoracotomy group (p = 0.2611). Inconsistencies between the clinical and pathological stages were mainly related to tumor size, nodal status, and pleural invasion. Local recurrence occurred for one lesion in the VATS group and six lesions (five patients) in the thoracotomy group (p = 0.0495). CONCLUSIONS: The DFS and OS were not inferior after VATS compared with thoracotomy. Local control was significantly better after VATS than after thoracotomy. Preoperative staging lacked sufficient accuracy.